Analysis of Quality Control Using the Failure Mode And Effect Analysis (FMEA) Method in the Welding Process in the Feed Drum Project - Rizkia Maulindah Lisna; Efta Dhartikasari Priyana; Hidayat Hidayat (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
PT. Xyz is a steel fabrication company located in Gresik. One of their projects undertaken by PT. XYZ is a Feed drum Project, the welding process is the most important stage in this project. At the time of product testing or testing there were still many welding points that were defective so that the product did not pass the trial, the trial was carried out by hydrotest where this test was carried out with water as the test medium to determine the strength of a material and find out whether there was a leak or not and as well as a visual check. The types of defects found in the feed drum project are spatter, overlap, porosity, undercut, incomplete fusion, slag, bad String Bead (Weaving Fault), start stop, pin hole. The research uses the FMEA (Failure Mode Effects and Analysis) the method which aims to identify and analyze the occurrence of defects. In the results, the highest RPN value is found in the Incomplate Fusion type of defect with a value of 384 so that it becomes a priority in carrying out control and repair .